ANALISIS ASAS ULTRA PETITUM PARTIUM DALAM PERKARA CERAI TALAK No. 30/Pdt.G/2016/PA.Prg. DI PENGADILAN AGAMA PINRANG KELAS IB - Rahmatullah, Muhammad Ahmad (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2018)
The study examines The ultra petitum partium principle in the divorce case No.30/Pdt.G/2016/PA.Prg. at Pinrang Class 1B Religious Court, based on the implementation analysis of ultra petitum partium principle in the divorce case No.30/Pdt.G/2016/PA.Prg. at Pinrang Class1B Religious Court, still on the right track although deviating from what has been outlined in the Islamic Law Compilation (ILC) as in the petitum of the Judge’s petition punishes the former husband by imposing the living of iddah and mut'ah based on the ex officio right of the judge in the marriage which is legally no relationship occured between husband and wife (qabla al-dukhūl) whereas the provisions of the judge may exclude the prohibition of imposing a verdict beyond the demands of the parties if the case has occurred an intercourse (ba’da al-dukhūl) as contained in (ILC) article 149 letters (a) and (b), on the consequences of the breaking up of marriage. While the basic consideration of judges used in the divorce case No.30/Pdt.G/2016/ PA.Prg among others: 1) Marriage Act (Act No. 1 of 1974) is a lex specialis rule, 2) Judges have the authority to creating law (judge made law), 3) The judge’s considered faktor de facto to grant the petition whithout claim (4) Compilation of Islamic Law, article 149 letters (a) and (b), on the results of marriage breakup.